2015
DOI: 10.2527/jas.2015-9048
|View full text |Cite
|
Sign up to set email alerts
|

Mean pulmonary arterial pressures in Angus steers increase from cow–calf to feedlot–finishing phases1

Abstract: Pulmonary arterial hypertension due to hypoxia-induced pulmonary vascular remodeling is the predominant cause of right-sided congestive heart failure (CHF) in cattle. Historically, heart failure was problematic only at altitudes over 2,134 m. However, anecdotal reports suggest that the incidence of heart failure is increasing in feedlot cattle at moderate altitude (800 to 1,600 m), with late-fed, or fat, cattle at greatest risk. The goal of this study was to evaluate pulmonary arterial pressures (PAP) in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…We would, therefore, anticipate that the mPAP of calves at the moderate altitude of 975 m to be lower than the mPAP of similarly aged calves located at a higher altitude. The values recorded in our study, however, are greater than those observed in 6-mo-old male Black Angus calves at an altitude of 2,170 m (42 mm Hg; Neary et al, 2015 ) and only slightly less than 6-mo-old crossbred Angus heifers (51 mm Hg) and steers (54 mm Hg) at an altitude of 2,730 m ( Neary et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…We would, therefore, anticipate that the mPAP of calves at the moderate altitude of 975 m to be lower than the mPAP of similarly aged calves located at a higher altitude. The values recorded in our study, however, are greater than those observed in 6-mo-old male Black Angus calves at an altitude of 2,170 m (42 mm Hg; Neary et al, 2015 ) and only slightly less than 6-mo-old crossbred Angus heifers (51 mm Hg) and steers (54 mm Hg) at an altitude of 2,730 m ( Neary et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 88%
“…Feedlot cattle treated for bovine respiratory disease ( BRD ) were three times more likely to die of congestive right heart failure than cattle that did not require treatment ( Neary et al, 2016a ). It has also been determined that cattle with the greatest mPAP as suckling calves typically have the greatest mPAP through the confined feeding phase ( Neary et al, 2015 ); consequently, interventions that reduce mPAP in the cow–calf phase may have beneficial carryover health effects as cattle enter the next phase of production.…”
Section: Introductionmentioning
confidence: 99%
“…In that same study, localized hypoxia resulting from respiratory disease was a risk factor, given that cattle treated for respiratory disease were 2-3 times more likely to die of RHF than cattle not treated for respiratory disease. 21 Although high altitude is a well-established factor, previous studies 15,20,21 indicate that obesity and potentially coronary artery disease and left-heart dysfunction are likely major contributing factors to pulmonary hypertension and right-sided heart failure, and may have played a role in disease in the cattle in our study. Cattle are now fed to heavier finishing weights, with abdominal fat accumulation causing hypoxia through hypoventilation.…”
Section: Discussionmentioning
confidence: 64%
“…In general, cattle are more susceptible to hypoxia-induced pulmonary hypertension than are other species. 20 At least in part, cattle are prone to hypoxemia because they have small lungs relative to their oxygen requirements. 8 A 2016 large-scale study involving midwestern high plains feedyards in the United States and Canada found that cattle of different breeds developed RHF at moderate altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of pulmonary hypertension occurring in feedlot cattle is identified as feedlot heart disease (FHD). FHD can cause late-term feedlot death ( Jensen et al, 1976 ; Neary et al, 2015a , 2015b ). Common symptoms of HMD and FHD include, but are not limited to, jugular vein distension, edema, and lethargy.…”
Section: Introductionmentioning
confidence: 99%